2017
DOI: 10.1038/s41598-017-01297-z
|View full text |Cite
|
Sign up to set email alerts
|

A 2-oxa-spiro[5.4]decane scaffold displays neurotrophic, neurogenic and anti-neuroinflammatory activities with high potential for development as a versatile CNS therapeutic

Abstract: 1,5Following our recent discovery of a new scaffold exhibiting significant neurotrophic and neurogenic activities, a structurally tweaked analogue, embodying a 2-oxa-spiro [5.4]decane framework, has been conceptualised and found to be more potent and versatile. It exhibits enhanced neurotrophic and neurogenic action in in vitro, ex vivo and in vivo models and also shows robust neuroprotection in mouse acute cerebral stroke model. The observed attributes are traceable to the predominant activation of the TrkB-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…The neurogenesis potential has been shown to be affected in animal models of neuropsychiatric disorders, including chronic stress models, 29 32 and this potential is assessed using ex vivo neurosphere culture assay. 33 Therefore, to evaluate the neurogenic ability of compounds (comp #A–D), the hippocampi were removed from neonatal mice, and the hippocampal neural stem and/or progenitor cells (NSCs/NPCs) collected therefrom were grown in the culture medium as neurospheres. The effects of all of the compounds (comp #A–D) were studied at various concentrations (1.0–0.01 μM) for induction of neurosphere formation in NSCs/NPCs, resulting in moderately sized neurospheres (>100 μm).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The neurogenesis potential has been shown to be affected in animal models of neuropsychiatric disorders, including chronic stress models, 29 32 and this potential is assessed using ex vivo neurosphere culture assay. 33 Therefore, to evaluate the neurogenic ability of compounds (comp #A–D), the hippocampi were removed from neonatal mice, and the hippocampal neural stem and/or progenitor cells (NSCs/NPCs) collected therefrom were grown in the culture medium as neurospheres. The effects of all of the compounds (comp #A–D) were studied at various concentrations (1.0–0.01 μM) for induction of neurosphere formation in NSCs/NPCs, resulting in moderately sized neurospheres (>100 μm).…”
Section: Resultsmentioning
confidence: 99%
“… 64 The social avoidance behavior of the stressed zebrafish, indicative of depression-like phenotype, was assessed by the social interaction test based on the approach and interaction behavior toward an unfamiliar conspecific target (pink-colored zebrafish) as reported. 33 Briefly, experimental zebrafish were introduced into the tank with the target in the interaction box for 120 s, a conspecific pink-colored zebrafish served as a target animal in the interaction zone. The entire test was video-recorded with a Sony Handycam Camcorder 200E in HD mode, and the data were scored manually.…”
Section: Methodsmentioning
confidence: 99%
“…A separate group of animals (XY RIII and XY RIII qdel, 4–5 in each group), were injected with BrdU (50 mg/Kg, intraperitoneally), a thymine analog that gets incorporated in DNA of proliferating cells, twice daily starting 2 days prior to the sacrifice. The mice were intra-cardially perfused with paraformaldehyde and brains were collected and processed for immunostaining as reported earlier (Suri et al, 2013 ; Chakravarty et al, 2015 ; Joshi et al, 2017 ) with minor modifications. In brief, Vectastain ABC kit (Vector Labs) was used and sections were developed with diaminobenzidine (DAB) before mounting in DPX to count BrdU positive cells observed in sub granular zone of hippocampus.…”
Section: Methodsmentioning
confidence: 99%
“…The synthesized natural product derivatives (1a, 4-9 and 4a-9a) were evaluated for their in vitro cell cytotoxicity against mouse neuroblastoma cells (Neuro 2a) by using 3-(4,5dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. 12,13 The results of in vitro cytotoxicity revealed that the tested compounds were relatively less cytotoxic as compared to the untreated control (see the supplementary information). This preliminary observation was promising to explore the neurotrophic potential in Neuro2a cells using standard in vitro protocol.…”
Section: Scheme 3: Synthesis Of Triazole Derivatives Of 1 and 1amentioning
confidence: 99%
“…This preliminary observation was promising to explore the neurotrophic potential in Neuro2a cells using standard in vitro protocol. 12 Initially, neurite outgrowth assay was performed to investigate the neurotrophic potential of natural product derivatives (1a, 4-9, 4a-9a). In this study, the Neuro 2a Cells were serum starved for 6 hours and were exposed to the synthesized compounds (1a, 4-9, 4a-9a) along with Nerve growth factor (NGF) as a positive control at concentrations of 0.1 µM and 0.01 µM for 48 hours.…”
Section: Scheme 3: Synthesis Of Triazole Derivatives Of 1 and 1amentioning
confidence: 99%